2023
DOI: 10.3389/fendo.2023.1131171
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mRNA-miRNA-lncRNA differential expression in prediabetes/type 2 diabetes mellitus patients as potential players in insulin resistance

Abstract: IntroductionType 2 diabetes mellitus (T2DM) is a major global health concern. It usually develops gradually and is frequently preceded by undetectable pre-diabetes mellitus (pre-DM) stage. The purpose of this study was to identify a novel set of seven candidate genes associated with the pathogenesis of insulin resistance (IR) and pre-DM, followed by their experimental validation in patients’ serum samples.MethodsWe used the bioinformatics tools and through a two-step process, we first identified and verified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…43 As a result, it is imperative to investigate the mechanism and pinpoint molecular targets for prompt diagnosis and treatment. 44 The pathogenesis of T2DM is very complex and involves inflammatory and immune reactions, epigenetic modulations, and signaling pathways. 43 Additionally, medication noncompliance due to side effects is a major limitation in T2DM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…43 As a result, it is imperative to investigate the mechanism and pinpoint molecular targets for prompt diagnosis and treatment. 44 The pathogenesis of T2DM is very complex and involves inflammatory and immune reactions, epigenetic modulations, and signaling pathways. 43 Additionally, medication noncompliance due to side effects is a major limitation in T2DM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs can influence insulin signaling by affecting the expression of INSR and IRS-1, the translocation of GLUT4, and the activity of PI3K; furthermore, they influence insulin secretion by regulating β-cell metabolic stress, proliferation, and survival, as well as regulating GSIS and improving insulin sensitivity [148][149][150][151]. Therefore, miR-NAs are potential biomarkers for diabetes prediction [152]. A meta-analysis revealed that miR-29a-3p, miR-221-3p, miR-126-3p, miR-26a-5p, miR-503-5p, miR-100-5p, miR-101-3p, mIR-103a-3p, miR-122-5p, miR-199a-3p, miR-30b-5p, miR-130a-3p, miR-143-3p, miR-145-5p, miR-19a-3p, and miR-311-3p (in order of importance) fulfill the criteria for biomarker selection [153].…”
Section: Microrna (Mirna)mentioning
confidence: 99%
“…Ali and collaborators studied the serum levels of miRNAs, mRNAs, and lncRNAs (long noncoding RNAs) in subjects with type-2 diabetes, subjects with prediabetes, and healthy control subjects, with the purpose of identifying genes broadly related to the pathogenesis of insulin resistance and prediabetes. The results showed that the expression levels of TMEM173 (Transmembrane Protein 173), CHUK (Conserved Helix-loop-helix Ubiquitous Kinase), and the miRNAs miR-611, miR-5192, and miR-1976 gradually increased from the control group to the prediabetes group and reached their highest levels in the type-2 diabetes group, while the expression of lncRNAs RP4-60503.4 and AC074117.2 gradually decreased from the control group to the prediabetes group and reached their lowest levels in the type-2 diabetes group [55].…”
Section: Insulin Resistancementioning
confidence: 99%